An Ionophore‐Based Anion‐Selective Optode Printed on Cellulose Paper. (16th August 2017) - Wang, Xuewei; Zhang, Qi; Nam, Changwoo; Hickner, Michael; Mahoney, Mollie; Meyerhoff, Mark E.
Abstract: A general anion‐sensing platform is reported based on a portable and cost‐effective ion‐selective optode and a smartphone detector equipped with a color analysis app. In contrast to traditional anion‐selective optodes using a hydrophobic polymer and/or plasticizer to dissolve hydrophobic sensing elements, the new optode relies on hydrophilic cellulose paper. The anion ionophore and a lipophilic pH indicator are inkjet‐printed and adsorbed on paper and form a "dry" hydrophobic sensing layer. Porous cellulose sheets also allow the sensing site to be modified with dried buffer that prevents any sample pH dependence of the observed color change. A highly selective fluoride optode using an Al III ‐porphyrin ionophore is examined as an initial example of this new anion sensing platform for measurements of fluoride levels in drinking water samples. Apart from Lewis acid–base recognition, hydrogen bonding recognition is also compatible with this sensing platform.